Contribution of Islamic scholars to sustainable human and environmental development: Islam hadhari and future development of muslim countries (2011)
Today, despite the global scientific and technological advancement with developed and even a few developing countries including Muslim countries making significant strides in shaping contemporary civilisation and the state of the world, yet they have failed to achieve true development and progress on how to sustain human and other creatures in a wholesome manner. This is because while these countries are struggling for scientific and technological development in order for humans to live a decent and comfortable life, they have not fully comprehended the underlying indexes that formed the basis of sustainable development. This paper therefore examines the teachings of Islam on the underlying indexes that formed the basis of sustainable development. It used the maqasid approach to show that in Islam development and progress are useful and desirable only when they improve upon and sustain not only human comfort and standards of living but also the essentials to achieving higher and enhanced quality of life for not only humans but also the environment and all the creatures cohabiting in it. It finally reveals how the maqasid approach in Islam sets out to achieve this real development.